Income inequality and the quality of imports - Andrea Ciani (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
This paper investigates how income inequality affects the quality of imported products. In a heterogeneous-firms trade model, I show that higher inequality increases total expenditure leading to a reduction in unit value and quality of imported goods. To test this prediction, I employ detailed firm-level trade data for the period 2001- 2006. I empirically document that higher inequality is associated with lower unit value and lower quality of imported products. This negative relation is due to firm-level heterogeneous responses to variations in total expenditure. Incumbent firms react to an increase in total expenditure caused by higher inequality lowering unit values, while firms entering the same market for the first time supply goods of lower quality.
Keywords: F14; L11; L15; O15; 330; Income Inequality; Unit Value; Quality; Trade